2015
DOI: 10.1590/1980-5497201500040014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados ao ganho de peso gestacional excessivo em unidades de saúde do sudoeste da Bahia

Abstract: ABSTRACT:Objective: To determine the prevalence of excessive gestational weekly weight gain and to identify its association with demographic, socioeconomic, obstetric, anthropometric, and behavioral characteristics. Methods: This cross-sectional study included 328 pregnant women attending all health units in the urban area of Vitória da Conquista, Bahia. The data were collected from May 2010 to June 2011. The weekly weight gain was evaluated according to the current recommendations of the Institute of Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
28

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
0
17
0
28
Order By: Relevance
“…16 These data observed for the general population in the country reflect the population of pregnant women, and many studies have observed a significant association between excess weight before the gestation and a greater frequency of excessive GWG. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 These data observed for the general population in the country reflect the population of pregnant women, and many studies have observed a significant association between excess weight before the gestation and a greater frequency of excessive GWG. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 Estes dados observados para a população geral no país refletem na população de gestantes, e muitos trabalhos observaram associação significativa entre excesso de peso antes da gestação e maior frequência de GPG excessivo. 17 …”
Section: Discussionunclassified
“…A associação positiva entre ganho excessivo de peso e a presença de companheiro pode ser explicada pelo contexto de maior apoio familiar que tais mulheres recebem o que pode ser um fator favorável ao consumo energético excessivo. Assim, justifica-se o monitoramento do ganho de peso, já que o ganho ponderal em excesso e a obesidade na gravidez estão intimamente relacionados com maiores riscos adversos para a mãe e recémnascido no pós-parto, além de promover o aumento dos marcadores inflamatórios durante a gestação, devendo ser evitado 6,23 .…”
Section: Revista Saúde E Pesquisaunclassified
“…A avaliação dietética da gestante por meio de inquéritos alimentares é importante, pois possibilita detectar problemas nutricionais específicos já existentes, que podem ser prejudiciais no decorrer da gestação. Para tanto, é fundamental o cuidado e atenção nutricional à saúde da mulher durante a gravidez, à saúde do concepto, ao bem-estar materno para possibilitar a nutrição do recém-nascido e à proteção contra o desenvolvimento de doenças crônicas durante a vida adulta 6 .…”
Section: Introductionunclassified
See 1 more Smart Citation